The namesake - Lahiri, Jhumpa (New York, NY Houghton Mifflin, 2003)
When his Indian immigrant parents give him an odd name, a boy must struggle towards manhood suffering the burdens of this name as well as the conflicting loyalties of his heritage
Php 700.00
Donated by Gorriceta-Rojo family 12.11.18
Keywords: GogolÊ¹, NikolaÄ VasilÊ¹evich, 1809-1852 -- Appreciation -- Fiction; Young men -- Fiction; Massachusetts -- Fiction; East Indian Americans -- Fiction; Children of immigrants -- Fiction; Assimilation (Sociology) -- Fiction; Alienation (Social psychology) -- Fiction; Domestic fiction